Report of the Conference on Disarmament: 2016 Session - United Nations Department for General Assembly; Conference Management (United Nations)
The Conference on Disarmament submits to the seventy-first session of the General Assembly of the United Nations its annual report on its 2016 session, together with the pertinent documents and records.